A systematic review of mindfulness-based interventions for substance use disorders - De Villiers, Danielle (https://orcid.org/0009-0007-9596-8784) (Rhodes University, 2026)
Embargo applied. Embargo period to expire in March of 2027.
cannabis and methamphetamine
Keywords: Substance abuse (http://id.loc.gov/authorities/subjects/sh85129539); Cannabis (http://id.loc.gov/authorities/subjects/sh85019610); Methamphetamine abuse (http://id.loc.gov/authorities/subjects/sh99013490); Clinical Psychology